Prognostic Value of Inflammatory and Tumour Markers in Small-Duct Subtype Intrahepatic Cholangiocarcinoma after Curative-Intent Resection - Bingqi Ma; Huijuan Meng; An Shen; Yuwen Ma; Dianpeng Zhao; Guiling Liu; Shujuan Zheng; Ye Tian; Wei Zhang; Qiang Li; Shiping Li (Gastroenterology Research and Practice)
Intrahepatic cholangiocarcinoma (ICC) is characterised by heterogeneity, and it can be subdivided into small-duct and large-duct types. Inflammatory and tumour markers could effectively predict prognosis in many cancers, but no similar studies have been conducted in the histological subtypes of ICC. A total of 102 and 72 patients with ICC undergoing curative-intent resection were retrospectively subclassified into large-duct and small-duct types by chemical staining, respectively. The prognostic value of inflammatory and tumour markers was studied for the first time in histological subtypes of ICC by using a Cox regression model. A novel predictor named prognostic inflammatory index (PII) was proposed and defined as neutrophil×monocyte/lymphocyte count (109/L). Survival analysis showed that PII, neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9), CA242, and ferritin were all predictors of DFS and OS in patients with ICC (P<0.040). Subgroup analysis showed that PII, CA19-9, and ferritin were risk predictors of disease-free survival (DFS) and overall survival (OS) in small-duct type ICC (P<0.015). In addition, in small-duct type ICC, NLR and LMR were correlated with OS (P<0.025), whilst CEA and CA242 were correlated with DFS (P≤0.010). In conclusion, PII is a convenient and efficient inflammatory predictor of DFS and OS in ICCs and their small-duct type. NLR and LMR, rather than platelet-to-lymphocyte ratio, were correlated with OS in small-duct type ICC. In addition, ferritin may be a supplement to CA19-9 in stratifying the survival outcome of patients with small-duct type ICC.